Features of the evolutionary transition/transversion bias of birds and mammals by the CYTB gene - Mezhzherin, S.V.; Morozov-Leonov, S.Yu. (Доповіді НАН України, 2024)
Differences in the nature of the transition/transversion bias of birds and mammals, as well as families with small and large body-sized species, are proven by the example of the CYTB gene. It was that for birds compared to mammals, as well as in families of small birds and mammals compared to larger ones, the frequency of transversions is signifi cantly higher and the frequency of transitions is lower. Th is leads to a decrease in the transition/transversion bias and a decrease in the rate of its evolutionary compensation. Th e possible cause of this phenomenon is the greater intensity of individual metabolism and the resulting increase in mutation rates in birds and small species. Exceptions are extremely small species that are characterized by a state of hypothermia. Th e high level of metabolism and mutability explains the richness of bird species, as well as the highest activity of speciation in small organisms. In addition, the transition/transversion bias should be considered as a reliable integral indicator of individual metabolic intensity at the family level.